The Development of an Agricultural Union in Mali : Increasing Levels of Local Empowerment - Easton, Peter; Belloncle, Guy; Coulibaly, Cheibane; Fass, Simon; Moussa, Laouali Malam (World Bank, Washington, DC, 2012)
In the early 1990s, the village associations (AV) in the Koutiala regions of southern Mali had an issue to sort out with the Malian Textile Company (CMDT) and won the case. Encouraged by the success, they united efforts again to address other problems and evolved into a union (SYCOV). The SYCOV represents a second stage in local empowerment in rural areas of southern Mali and illustrates some of the benefits possible through the actual transfer of economic authority into the hands of farmers' associations.